The Challenge of Teaching Essential Immunology Laboratory Skills to Undergraduates in One Month—Experience of an Osteoimmunology Course on TLR Activation - de Vries, Teun J.; Schoenmaker, Ton; van Veen, Henk A.; Hogervorst, Jolanda; Krawczyk, Przemek M.; Moonen, Carolyn G. J.; Jansen, Ineke D. C. (Frontiers in Immunology, 2019)
Acquiring immunology laboratory skills during undergraduate studies is often a prerequisite for admission to Masters’ programs. Many broad liberal arts and sciences honors degree colleges struggle in teaching these essentials since only limited time is usually reserved for this. Here, we describe a new one-month-course developed to train a small group of honors students in 6 techniques that are useful for immunology research. In essence, 15 students were divided into 3 groups of 5 students where each student became involved in current osteoimmunology research. Osteoimmunology is a relatively new branch onf the immunology tree, where the effects of inflammation and the immune system on bone formation and bone degradation is studied. A broad, 3 weeks experiment on the chronic effects of molecules that specifically activate toll-like receptors TLR2 and TLR4 on bone formation or osteoclast differentiation was performed just before the start of the course. Control samples and samples treated with TLR2 (group A), TLR4 (group B), or TLR2+TLR4 (group C) agonists were harvested and analyzed using quantitative PCR, ELISA, biochemistry, microscopy of enzyme-histochemically stained osteoclasts, scanning electron microscopy and confocal microscopy. Each technique was taught for two days by a specialized instructor, who was present at all laboratory activities. The primary research question for each group was: how does the experimental condition affect bone formation or osteoclast formation? The secondary research question per technique was: how does this technique answer part of the primary research question? Pedagogically, students were encouraged to collaborate within the group to analyze the obtained data. Secondly, at the end of the course, a representative of each group collaborated to summarize the TLR activation modalities of a technique of choice. Thirdly, each group wrote a report, where introduction and discussion were graded as a group; each technique part was graded individually. The summary of the results from the 3 treatment modalities was presented orally. The course evaluation was high, students remarked that the course had a curriculum overarching function, since it created an awareness and appreciation for both the joy and the blood-sweat-and-tears aspects of pipetting and writing research articles, making interpretation of those easier.